Karakteristik Peternak Sapi Peranakan Ongole Dan Keberhasilan Inseminasi Buatan Berdasarkan Service Per Conception Di Kabupaten Lampung Selatan - Sutarno, Sutarno; Wati, Novi Eka; Setyowati, Sari (JDP: Jurnal Dunia Peternakan, 2023)
The success of artificial insemination is determined by three main factors namely; livestock, cement and humans. The human factor is one of the determining factors, especially the characteristics of farmers. The purpose of this study was to determine the characteristics of cattle farmers and the success of artificial insemination based on Service per Conception (S/C) in Palas Sub District, South Lampung District. This research was conducted in Palas Sub District, South Lampung District. The time of research was in July 2023. The material for this research was ongole cattle farmers in Palas Sub District, namely 150 cattle famers. The research sample is 60 cattle famers. The research method used is survey method. The data analysis technique uses descriptive analysis, namely analysis to explain the characteristics of cattle farmers and the success of insemination based on Service per Conception (S/C). The results of the research on the characteristics of onggole cattle farmers in Palas Sub District, South Lampung District, obtained an average age of famers cattle was 42.53, the level of education of cattle famers was mostly junior high school (SMP) and high school (SMA), the average length of time they raised cattle average 7.08 years, and there were no farmers who had ever been involved in animal husbandry training. The success rate of artificial insemination in ongole crossbreed cattle based on service per conception (S/C) obtained an average value of S/C = 1.54.